AB0581 Infliximab Therapy in Patients with Refractory Uveitis of Behçet's Disease: A Meta-Analysis. (15th July 2016) - Qin, Y.; Zhang, X.; Geng, P.; Luo, R.; Zhang, G.
Abstract : Background: Behçet's disease is a chronic inflammatory vasculitis that can affect multiple systems. Ocular involvement is common and often cause significant morbidity, such as loss of sight, and offering challenge to management due to relapse. Off-label use of anti-tumor necrosis factor (TNF) agents for Behçet's disease (BD) is increasing. Especially for refractory uveitis Objectives: To assess the effect of infliximab on refractory uveitis caused by Behçet's disease, we conducted a meta-analysis. Methods: A comprehensive search of multiple databases was performed. Weighted Mean Difference (WMD) or standardized mean difference (SMD) and 95% confidence intervals (95%CI) were calculated to assess the efficacy. Q test was used to examine the inter-study heterogeneity, and the robustness of the results was tested through sensitivity analysis. Begg's funnel plot and Egger's test were operated to check the publication bias. Results: A total of 9 articles were included in this meta-analysis. We observed that infliximab treatment significantly reduced uveitis attack in Behçet's disease patients (WMD=2.35, 95% CI: 1.74–2.96), which was confirmed by subgroup analysis on 6- and 12- month after treatment (WMD=2.51, 95% CI: 1.81–3.21; WMD=2.11, 95% CI: 0.62–3.60). Visual acuity was greatly improved by infliximab therapy (SMD=-0.31, 95% CI: -0.59 to -0.03). Moreover, infliximab therapy also decreased the macular thickness of Behçet's disease patients (SMD=1.75, 95% CI: 1.35–2.15). Conclusions: Infliximab therapy is effective in the treatment of Behçet's disease patients with refractory uveitis. Disclosure of Interest: Y. Qin Employee of: Yuxing Qin is employee of XIAN Janssen. The Janssen pharmaceutical companies did not provide any financial support for this work. The authors report no other conflicts of interest., X. zhang: None declared, P. Geng: None declared, R. luo: None declared, G. zhang: None declared